Dietary supplementation of 25-hydroxycholecalciferol improves cardiac function and livability in broiler breeder hens–amelioration of blood pressure and vascular remodeling - Yeh, Yo-Lin; Chou, Pao-Chia; Chen, Yu-Hui; Lai, Lih-Shiuh; Chung, Thau Kiong; Walzem, Rosemary L.; Huang, San-Yuan; Chen, Shuen-Ei (Poultry science, 2020)
A supplement of 69 μg 25-hydroxycholecalciferol (25-OH-D3)/kg feed suppressed the mortality in feed-restricted broiler breeder hens and in hens allowed ad libitum feed intake (Ad-hens) in a feeding trial from age 26 to 60 wk. Outcomes for the mechanisms found that 25-OH-D3 relieved systemic hypoxia, pathological cardiac remodeling and arrhythmias, and hepatopathology to improve hens' livability. In the study, we further evaluated the effect of 25-OH-D3 on blood pressure and vascular remodeling relative to cardiac pathogenesis of sudden death (SD). Ad libitum feed intake increased mechanical loading and contributed to maladaptive cardiac hypertrophy as evidenced by consistently elevated peripheral arterial blood pressure in Ad-hens before SD (P < 0.05). In planned longitudinal measurements, Ad-hens also showed higher right ventricle systolic pressure and right ventricle diastolic pressure (RVDP) (P < 0.05). Supplemental 25-OH-D3 relieved peripheral hypertension and prevented time-dependent increases of RVDP in Ad-hens through the renin–angiotensin system and circulating nitric oxide availability and by regulating vascular remodeling including elastin/collagen ratio and smooth muscle cell proliferation in the pulmonary artery for improved elasticity/stiffness (P < 0.05). The antihypertensive effect via the renin–angiotensin system and nitric oxide regulation in respect to heart rate and arrhythmias by 25-OH-D3 were further confirmed in 51 week-old feed-restricted broiler breeder hens challenged with salt loading for 5 wk. Despite feed restriction, the most feed-efficient hens of feed-restricted groups also exhibited cardiac pathological hypertrophy, in conjunction with higher right ventricle systolic pressure, RVDP, plasma nitric oxide levels, and more dramatic arterial remodeling (P < 0.05). These results suggest that peripheral and pulmonary hypertension are the key drivers of SD and that 25-OH-D3 is an effective antihypertensive supplement to alleviate cardiac pathogenesis and improve livability in broiler breeder hens.